Innovation at One Acre Fund : seeing the forest for the trees - Jones, Jamie; Augustine, Grace ([London] : SAGE, 2016)
One Acre Fund (1AF) is a nonprofit organization in rural Western Kenya that helps farmers lift themselves out of poverty by providing a bundle of products and services that support farmers with quality inputs, training on farming techniques, access to credit and assistance in achieving optimal prices. The organization prides itself on its innovative culture, and always strives to offer new products and methods to its farmers. This case examines 1AF's continuous improvements.
Originally Published in: Jones, J., & Augustine, G. (2014). Innovation at One Acre Fund: Seeing the Forest for the Trees (case revised 15/102014; teaching note revised 03/11/2014). 5-114-002. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; One Acre Fund (Organization); Social entrepreneurship -- Case studies; Nonprofit organizations -- Management -- Case studies